Preparation and Biocompatibility of Poly Methyl Methacrylate (PMMA)-Mesoporous Bioactive Glass (MBG) Composite Scaffolds - Irina Atkinson; Ana Maria Seciu-Grama; Oana Catalina Mocioiu; Ana Maria Mocioiu; Luminita Predoana; Mariana Voicescu; Jeanina Pandele Cusu; Ramona Marina Grigorescu; Rodica Mariana Ion; Oana Craciunescu (Gels, 2021)
In recent years, the rising number of bone diseases which affect millions of people worldwide has led to an increased demand for materials with restoring and augmentation properties that can be used in therapies for bone pathologies. In this work, PMMA- MBG composite scaffolds containing ceria (0, 1, 3 mol%) were obtained by the phase separation method. The obtained composite scaffolds were characterized by X-ray diffraction, infrared spectroscopy, and scanning electron microscopy. UV–Vis measurement and EDX analysis confirmed the presence of cerium ions in the composite scaffolds. Evaluation of the in-vitro biocompatibility using MTT assay showed that composite scaffold containing 1 mol% of ceria presented higher viability than control cells (100%) for concentrations ranging between 5 and 50% after 96 h of incubation.